The efficacy of a constructivist approach to the training of Chinese mathematics teachers - Fung, Chi-yeung (Curtin University, 2002)
This action research study was conducted to investigate the efficacy of a constructivist approach to the training of first-year Chinese student mathematics teachers in the Hong Kong Institute of Education where I am employed. A four-stage teaching model was designed, based on the learning theory of constructivism and taking into particular consideration the characteristics of Chinese learners: the maintenance of hierarchical and group harmony and high achievement motivation. In order to determine whether the application of this model in a methodology could alter the teaching beliefs of newly enrolled students, a two-phase procedure was employed. First-year students in each phase of the study were involved in solving a teaching problem. Through self-articulation, group- and class-discussions and self-reflection, the students were examined to determine any change in their beliefs about teaching mathematics. Prior beliefs about mathematics teaching, and beliefs held at the end of the methodology module were determined and compared in order to determine if new learning was in evidence. The creation of an authentic interactive learning environment to foster the kind of learning desired - a potentially safe, trusting and non-judgemental environment for free disclosure of students' opinions and feelings about mathematics teaching - was investigated. Data was generated by different quantitative and qualitative methods. Findings were cross-checked by a critical colleague and through my observation and reflections, and these were recorded as clearly, orderly, and accurately as possible. The first phase results were employed to inform and to improve the teaching of the same methodology module in the second phase.Findings in the two phases were indicative of the creation of a genuine social constructivist learning environment in which student teachers enjoyed their learning. Student teachers in the second phase implementation of my study indicated an understanding of their role in a constructivist classroom - to construct their own theories of teaching mathematics, to assist their peers in knowledge construction and to learn to learn. Student teachers in the two cohorts were found to hold entrenched constructivist beliefs about teaching mathematics. They agreed that the teacher's role was a facilitator of learning and that persistent questioning could alter knowledge about mathematics. However, at the conclusion of the module, the Phase I students seemed to re-adopt traditional approaches to teaching, whereas the Phase II students exhibited two different perspectives - an indication of the instability of their teaching beliefs. The Phase II student teachers, nevertheless, showed that they became more aware of sequencing the various interactive activities for their pupils in secondary schools. In the actual teaching, they professed their inability to realise their teaching ideals because of their inexperience in teaching and of the unexpected situations in the school settings. The present research study adds to the paucity of literature in two areas. First, the employment of a constructivist approach in the preparation of teachers of junior secondary mathematics (for pupils of age between twelve and fifteen), especially in the training of Chinese student mathematics teachers.Second, the study of a higher education lecturer conducting research to improve his/her own practice. Undeniably, further research on models to change student teachers' prior knowledge (about mathematics, about the nature of mathematics, and about the teaching and learning of mathematics), on factors affecting the instability of beliefs, and on models to facilitate continuous development of the teaching professionals are necessary if not exigent.